Short Communication: Optimization of extraction of sulfhydryl compounds from several legumes seeds in Indonesia with various ethanol concentrations - Sri Wardatun; Yahdiana Harahap; Abdul Mun'im; NOORWATI SUTANDYO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Wardatun S, Harahap Y, Mun’im A. 2020. Short Communication: Optimization of extraction of sulfhydryl compounds from several legumes seeds in Indonesia with various ethanol concentrations. Biodiversitas 21: 1060-1064. Leucaena leucocephala (Lam.) de Wit (petai Cina), Parkia speciosa Hassk. (petai), and Archidendron jiringa (Jack) I.C. Nielsen (jengkol) seeds extracts contain sulfhydryl compounds and have various therapeutic properties. The main objective of this research was to compare the effect of various ethanol concentration on the yield of extract and levels of sulfhydryl compounds from leguminous seeds. Dried seeds were macerated at room temperature (25°C) with a ratio of solids and solvents was 1:10. The solvent concentrations used were 30%, 50%, 70% and 96% ethanol. The yield of extract was expressed as the ratio of the weight of extract to the weight of dried seeds, the level of sulfhydryl compound was expressed as reduced L-glutathione (GSH) equivalent. The level of sulfhydryl compounds was determined by Ellman reagent and further analyzed using a spectrophotometer at 411 nm wavelength. Stink bean produced the highest yield of extract, while the highest level of sulfhydryl compounds was obtained from petai cina seed extract. The concentration of ethanol gave a significant difference to the yield of extract and the level of sulfhydryl compounds. The results showed that ethanol concentration affected the efficiency of the extraction of total sulfhydryl compounds and the yield of the extract on leguminous seeds.